Comparative Analysis of Dopaminergic and Cholinergic Mechanisms of Sensory and Sensorimotor Gating in Healthy Individuals and in Patients With Schizophrenia - Proshin, Andrey T. (Frontiers in Behavioral Neuroscience, 2022)
Sensory and sensorimotor gating provide early processing of information under conditions of rapid oncome of multiple stimuli. Gating deficiency is observed in various psychopathologies, in particular, in schizophrenia. However, in the general population there is also a significant proportion of people with low filtration rates who do not show a noticeable cognitive decline, The review article presents a comparative analysis of existing data on the peculiarities of cholinergic and dopaminergic mechanisms associated with lowering gating in healthy individuals and in patients with schizophrenia. Conclusions are drawn about the differences in gating mechanisms in cohorts with low filtration rates from the population of healthy and in schizophrenia.